Major Reforms in Electricity Pricing: Evidence from a Quasi-Experiment. Issue 644 (22nd September 2021) - Labandeira, Xavier; Labeaga, José M; Teixidó, Jordi J
Abstract: The global energy mix and cost structure of the power industry are experiencing a redefinition. Many countries are revamping electricity-pricing systems to guarantee fixed-cost recovery, often by raising the fixed charge of two-part tariff schemes. However, a key assumption of two-part tariff schemes and associated fixed-cost recoveries is that consumers discriminate fixed from marginal costs. We conduct a quasi-experiment with data from a major electricity price reform recently implemented in Spain and find robust evidence indicating that consumers fail to distinguish between fixed and marginal costs. As a result, policymakers are not achieving the goal of cost recovery.